EFNB2 haploinsufficiency causes a syndromic neurodevelopmental disorder. Issue 6 (15th March 2018) - Lévy, J.; Haye, D.; Marziliano, N.; Casu, G.; Guimiot, F.; Dupont, C.; Teissier, N.; Benzacken, B.; Gressens, P.; Pipiras, E.; Verloes, A.; Tabet, A.‐C.
Abstract : Ephrin B2, one of the ligand of the EphB receptors, is involved in a complex signaling pathway regulating the development of the nervous system, neuronal migration, erythropoiesis and vasculogenesis. We report a patient with a de novo variant in EFNB2 and a family in which segregates a 610‐kb deletion at chromosome 13q33 encompassing only ARGLU1 and EFNB2 genes. The de novo variant was observed in a patient with anal stenosis, hypoplastic left ventricle and mild developmental delay. The deletion was identified in 2 sibs with congenital heart defect and mild developmental delay. One of the affected sibs further had myoclonic epilepsy and bilateral sensorineural hearing loss. The carrier mother was apparently asymptomatic. Because EFNB2 is located in the subtelomeric region of 13q chromosome, we reviewed the previous reports of terminal 13q deletion. We suggest that haploinsufficiency of the EFNB2 could be at the origin of several clinical features reported in 13qter deletions, including intellectual disability, seizures, congenital heart defects, anorectal malformation and hearing loss. Abstract :